2022
DOI: 10.1111/jocn.16532
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of resilience on the relationship between perceived social support and burnout among Chinese palliative nurses

Abstract: Aims and objectives:To detect the mediating effect of resilience on the relationship between perceived social support and burnout in Chinese palliative nurses.Background: Palliative nurses are a group that is vulnerable to burnout. Perceived social support may contribute to decreasing palliative nurses' burnout and facilitating their personal resilience, and resilience may be associated with lower levels of burnout. However, these relationships were unclear in the Chinese context. Design:A cross-sectional desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Additionally, we found a negative relationship between COVID-19-related burnout and social support. This finding is supported by several previous studies where burnout was negatively correlated with occupational burnout [ 64 , 65 , 66 ]. Furthermore, a recent systematic review found that supervisor and coworker support reduces nurses’ burnout [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, we found a negative relationship between COVID-19-related burnout and social support. This finding is supported by several previous studies where burnout was negatively correlated with occupational burnout [ 64 , 65 , 66 ]. Furthermore, a recent systematic review found that supervisor and coworker support reduces nurses’ burnout [ 67 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, a huge number of nurses in all positions (e.g. nursing staff, nurse managers and advanced practice registered nurses) are plagued with poor states of psychological well‐being, such as mental disorders, occupational fatigue and job burnout (Cinar et al, 2021; García & Calvo, 2021; Zhang et al, 2022). According to Nursing Times in 2021, approximately two‐thirds of nurses in the UK suffered from mental health deterioration and over 50% of nurses claimed that the national and organizational‐level well‐being support was inadequate (Ford, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, a huge number of nurses in all positions (e.g. nursing staff, nurse managers and advanced practice registered nurses) are plagued with poor states of psychological well-being, such as mental disorders, occupational fatigue and job burnout (Cinar et al, 2021;García & Calvo, 2021;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, a recent study revealed a close and negative correlation between social support and COVID-19 pandemic-related PTSD risk [ 27 ]. Increasing evidence also posits the resilience mediates the interaction between social support and psychological problems [ 24 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%